An evaluation of various data pre-processing techniques with machine learning models for water level prediction - Tiu E.S.K.; Huang Y.F.; Ng J.L.; AlDahoul N.; Ahmed A.N.; Elshafie A. (Springer Science and Business Media B.V., 2023)
artificial neural network; data processing; decomposition analysis; machine learning; prediction; river water; support vector machine; water level; Dungun Basin; Malaysia; Terengganu; West Malaysia